Characterization of a pixelated silicon microdosimeter in micro-beams of light ions. (April 2020) - Pola, A.; Bortot, D.; Mazzucconi, D.; Fazzi, A.; Galer, S.; Kirkby, K.J.; Merchant, M.J.; Palmans, H.; Agosteo, S.
Abstract: The monolithic silicon telescope technology allows to produce solid state microdosimeters. A detector constituted by a matrix of pixels (2 μm in thickness) coupled with a deeper stage (about 500 μm in thickness) was designed, developed and characterized by comparing its response against Tissue Equivalent Proportional Counters (TEPCs) in different irradiation fields, showing promising results. Each pixel of the ΔE stage is a thin diode of 9 μm in diameter delimited by a guard ring of 14 μm in diameter. The aim of this work is the study of the charge collection efficiency of the single pixel of the silicon microdosimeter by irradiating a prototype at the micro-beam facility of the Ion Beam Center - IBC of the University of Surrey. Different light ions were exploited (protons, lithium ions and carbon ions) and scanned on different positions on and around a single pixel of the detector. The results show that the charge generated by events on the sensitive region of the ΔE stage is completely collected, while a charge collection efficiency lower than one characterizes the region between the central pixel and its guard ring. The guard ring delimits properly the sensitive region: no signals arise from events outside the 14 μm in diameter ring. Nevertheless, the microdosimetric distributions of the different charged particles highlight a minor distortion in terms of the absorbed dose. This latter result justifies the good agreement with TEPCs in terms of microdosimetric distributions in different hadrons beams described in previous works. Highlights: Double-stage silicon telescope for microdosimetry applications. Characterization of the charge collection efficiency with light ions. The microdosimetric spectrum is slightly influenced by the partial charge collection.